2018
DOI: 10.1016/j.jaci.2017.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of respiratory viruses in human airway epithelia reveals persistent virus-specific signatures

Abstract: Our results highlight the differential in vitro pathogenesis of respiratory viruses during the acute infection phase and their ability to persist under immune tolerance. These data help to appreciate the range of disease severity observed in vivo and the occurrence of chronic respiratory tract infections in immunocompromised hosts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
151
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(168 citation statements)
references
References 56 publications
15
151
2
Order By: Relevance
“…In fact, ALI epithelium was reported to demonstrate robust RSV replication (Villenave et al, ; Pickles, ), and the level of RSV load was similar to that observed in nasal washes from RSV infected infants (DeVincenzo et al, ) or after nasal challenge with RSV Memphis 37 strain to healthy subjects (Kelly et al, ). Thus, ALI epithelium is now being used as a model to study the behaviour of respiratory pathogens in human tissue (Essaidi‐Laziosi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, ALI epithelium was reported to demonstrate robust RSV replication (Villenave et al, ; Pickles, ), and the level of RSV load was similar to that observed in nasal washes from RSV infected infants (DeVincenzo et al, ) or after nasal challenge with RSV Memphis 37 strain to healthy subjects (Kelly et al, ). Thus, ALI epithelium is now being used as a model to study the behaviour of respiratory pathogens in human tissue (Essaidi‐Laziosi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The activity of the main epithelial ionic channels, such as CFTR, EnaC, Na/K ATPase, is preserved and the epithelia is shown to respond in a regulated and vectorial manner to the pro-inflammatory stimulus, TNF-a (27) . A large panel of Most importantly, MucilAir™ replicates the main function of the airway epithelial cells, the mucociliary clearance driven by synchronized cilia-beating, and has been successfully used for acute, long-term and chronic in vitro studies (16,17,28,29) . Given that MucilAir™ is functionally robust and successfully mimics human nasal epithelium, it is important to conduct a clinical trial with SSPCF in order to demonstrate the safety and efficacy of it in in vivo settings.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro assays were performed in a 3D reconstituted human nasal epithelium model, MucilAir™ (Epithelix Sàrl, Geneva, Switzerland) for its great potential as a model to test respiratory sensitizers (16,17) . For maintenance, inserts were incubated in 500µl of MucilAir™ culture medium in a CO 2 incubator (37ºC, 5% CO 2 , 100% humidity, Heracell).…”
Section: Biological Model (Test System) Used For the In Vitro Studiesmentioning
confidence: 99%
“…Additionally, there are also evidence of reduced type I (IFNβ) and III (IFNλ) interferon production due to type 2-skewed inflammation, which contributes to imperfect clearance of the virus resulting in persistence of viral components, or the live virus in the airway epithelium (Contoli et al, 2006;Hwang et al, 2019;Wark, 2019). Due to the viral components remaining in the airway, antiviral genes such as type I interferons, inflammasome activating factors and cytokines remained activated resulting in prolong airway inflammation (Wood et al, 2011;Essaidi-Laziosi et al, 2018). These factors enhance granulocyte infiltration thus prolonging the exacerbation symptoms.…”
Section: Increase Viral Susceptibility and Prolong Activation Of Inflmentioning
confidence: 99%